Nutrition and Environmental Pollution Extension Curriculum Improved Diet-Related Behaviors and Environmental Health Literacy. (March 2019) - Brewer, Dawn; Bellamy, Hannah; Hoover, Anna; Koempel, Annie; Gaetke, Lisa
Kentucky experiences some of the nation's worst health outcomes related to obesity, diabetes, high blood pressure, and other age-related chronic diseases linked with oxidative stress and inflammation, which in turn are associated with poor diet, lack of physical activity, and exposure to certain environmental pollutants. In the Commonwealth, deteriorating infrastructure, inappropriate waste disposal, and potential occupational injury related to mining, agriculture, and other regionally important industries exacerbate the need for residents to have basic knowledge of potential environmental health threats. Unfortunately, community-level understanding of the complex connections between environmental exposures and health is limited, with many Kentuckians unaware that the Commonwealth is home to 13 hazardous waste sites included in the United States Environmental Protection Agency Superfund National Priorities List (NPL). The NPL highlights priority sites for long-term remedial action to reduce environmental contaminants. To enhance the understanding of environmental health and protective actions, the University of Kentucky Superfund Research Center Community Engagement Core developed a 9-lesson extension curriculum "Body Balance: Protect Your Body from Pollution with a Healthy Lifestyle" (Body Balance) and partnered with Kentucky's Family and Consumer Sciences (FCS) Cooperative Extension Service to pilot the curriculum in Kentucky communities. FCS agents in 4 Kentucky counties delivered the Body Balance pilot study (18-31 participants per lesson). Pre- and post-lesson questionnaires revealed increased knowledge and awareness of the effects of environmental pollution on health and the protective role of dietary strategies. Focus group participants (n = 18) self-reported positive behavior changes because of increases in knowledge and leadership from their FCS agent. The Body Balance curriculum appeared to be a promising mechanism for raising environmental health and diet knowledge, as well as for promoting positive behavior changes among white, middle/older-aged women in rural Kentucky communities.